Ovarian epithelial tumors Study of 70 cases.: Value factor analysis forecast. Therapeutic results - Viola Alles, Alberto; Barrios, Enrique; Sabini, Graciela; Musé, Ignacio (Cirugía del Uruguay, 1992)
The author analyses 10 cases o/ epithelial tumors of the ovary whose average age was 54; and were stadified as follows: S /, 23 cases (33%), S 11, 17 cases (24%}, S 1/1, 20 cases (29%). S IV 10 cases (14%). Serous varieties were predominan/ (29 cases-42%); mucinous with 24 cases (34%); the rest were 8 endometroid ones, 7 anap/astic and one case of Clear and Brenner ce// tumor. Treatment